Relational neuroscience: insights from hyperscanning research - De Felice, Sara; Chand, Tara; Croy, Ilona; Engert, Veronika; Goldstein, Pavel; Holroyd, Clay B.; Kirsch, Peter; Krach, Sören; Ma, Yina; Scheele, Dirk; Schurz, Matthias; Schweinberger, Stefan R.; et al. (Neuroscience & biobehavioral reviews, 2025)
Humans are highly social, typically without this ability requiring noticeable efforts. Yet, such social fluency poses challenges both for the human brain to compute and for scientists to study. Over the last few decades, neuroscientific research of human sociality has witnessed a shift in focus from single-brain analysis to complex dynamics occurring across several brains, posing questions about what these dynamics mean and how they relate to multifaceted behavioural models. We propose the term ‘Relational Neuroscience’ to collate the interdisciplinary research field devoted to modelling the inter-brain dynamics subserving human connections, spanning from real-time joint experiences to long-term social bonds. Hyperscanning, i.e., simultaneously measuring brain activity from multiple individuals, has proven to be a highly promising technique to investigate inter-brain dynamics. Here, we discuss how hyperscanning can help investigate questions within the field of Relational Neuroscience, considering a variety of subfields, including cooperative interactions in dyads and groups, empathy, attachment and bonding, and developmental neuroscience. While presenting Relational Neuroscience in the light of hyperscanning, our discussion also takes into account behaviour, physiology and endocrinology to properly interpret inter-brain dynamics within social contexts. We consider the strengths but also the limitations and caveats of hyperscanning to answer questions about interacting people. The aim is to provide an integrative framework for future work to build better theories across a variety of contexts and research subfields to model human sociality.